Karakteristik Sampah Makroplastik di Pantai Wisata Lamaru Kota Balikpapan: Characteristics of Macroplastic at Lamaru Tourism Beach Balikpapan City - Ayla Nursari; Irwan Ramadhan Ritonga; Ristiana Eryati (LPPM Universitas Mataram, 2023)
Marine debris is one of the environmental problems in Indonesia's coastal and marine areas, especially macroplastics. One of the coastal areas with macroplastic problems is the tourist beach, which may adversely affect the coastal ecosystem, biota, and reduce the quality of the coastal environment. The purpose of this study was to identify the type and composition, calculate the total weight, and determine the difference in macroplastic density in two different periods. This study was conducted in March and August 2022 at Lamaru tourism beach, Balikpapan City, East Kalimantan. Transect lines and sampling at the research site were determined by following guidelines from the Ministry of Environment and Forestry of the Republic of Indonesia. Sampling was carried out in transect areas with a length of 100 metres parallel to the shoreline and following the width of the beach ridge. All data collected were analysed using Microsoft Office Excel and SPSS software. It was found that the types and composition of macroplastic at Lamaru tourism beach were 12 types such as bottle caps, spoons, food and beverage packaging, plastic bags, toys, cigarette butts, plastic basins, net bags, tarpaulins, rope, raffia, and other plastic materials with a total of 142 items. The total weight of macroplastic waste in period I was 5.6792 gr/m2 and in period II was 4.1874 gr/m2. There was no significant effect (p>0.05) between different periods on the amount, weight and density of microplastics at Lamaru Tourism Beach, Balikpapan City. The dominant source of macroplastic at Lamaru beach comes from human activities on land.